The Interaction Between Dietary Fructose and Gut Microbiota in Hyperuricemia and Gout - Fang, Xin-yu; Qi, Liang-wei; Chen, Hai-feng; Gao, Peng; Zhang, Qin; Leng, Rui-xue; Fan, Yin-guang; Li, Bao-zhu; Pan, Hai-feng; Ye, Dong-qing (Frontiers in Nutrition, 2022)
With the worldwide epidemics of hyperuricemia and associated gout, the diseases with purine metabolic disorders have become a serious threat to human public health. Accumulating evidence has shown that they have been linked to increased consumption of fructose in humans, we hereby made a timely review on the roles of fructose intake and the gut microbiota in regulating purine metabolism, together with the potential mechanisms by which excessive fructose intake contributes to hyperuricemia and gout. To this end, we focus on the understanding of the interaction between a fructose-rich diet and the gut microbiota in hyperuricemia and gout to seek for safe, cheap, and side-effect-free clinical interventions. Furthermore, fructose intake recommendations for hyperuricemia and gout patients, as well as the variety of probiotics and prebiotics with uric acid-lowering effects targeting the intestinal tract are also summarized to provide reference and guidance for the further research.